Synthesis of polycrystalline Ta₂O₅ inverse opal photonic crystal powders and their optical characterization - Taiki Maekawa; Hiroyuki Maekawa; Yuto Ikeda; Tomoya Onoe; Geoffrey I.N. Waterhouse; Kei-ichiro Murai; Toshihiro Moriga (Open Ceramics)
Polycrystalline Ta2O5 inverse opal (IO) photonic crystal powders were synthesized using PMMA colloidal crystals as sacrificial templates. We prepared Ta2O5 IO powders with vibrant structural colors at UV–vis wavelengths. The photonic bandgaps (PBGs) in the Ta2O5 IO powders red-shifted as a function of both the macropore diameter and the refractive index of the medium filling the macropores. Owing to their polycrystalline structure, the Ta2O5 IO powders exposed PBGs for various FCC facets, making investigation of their optical properties significantly more complex than Ta2O5 IO thin films that preferentially expose only (111) planes as studied previously. Due to the overlap of the PBGs from different FCC facets and the defects that cause light scattering, much of the typical angle-dependent structural color observed in IO thin films was lost in the Ta2O5 IO powders. This study offers new insights into the optical properties of IO powders.